Merawat Alam, Menjaga Kesehatan, Inisiatif Tanam TOGA dan Bunga oleh Mahasiswa KKN Kelompok Asoka dan Masyarakat Jorong Koto Panjang - Putra, Rido; Febmy, Dara Welisa; Rafki, Muhammad; Putri, Febri Yola; Sofiah, Iffatus; Puput, Puput (Lembaga Yasin AlSys, 2026)
The planting program for Tanaman Obat Keluarga (TOGA; family medicinal plants) and ornamental flowers was a collaborative initiative between students of the Kuliah Kerja Nyata (KKN) Asoka Groups 1–4 and the community of Jorong Koto Panjang, aimed at improving environmental quality while fostering awareness of nature conservation based on citizen participation. This community service activity was implemented through TOGA planting every Saturday morning in Taman Asoka and ornamental flower planting in the afternoon at various strategic locations in the surrounding area. The results of the program’s implementation showed a significant increase in community participation, improvements in environmental aesthetics, and the development of collective awareness regarding the importance of sustainable environmental conservation. The program successfully created a positive synergy between students and the local community in realizing a healthy and green environment, while also providing a replicable model for environment-based community service programs in other regions.